Role of cereblon in angiogenesis and in mediating the antiangiogenic activity of immunomodulatory drugs. Issue 9 (17th July 2020) - Beedie, Shaunna L.; Huang, Phoebe A.; Harris, Emily M.; Strope, Jonathan D.; Mahony, Christopher; Chau, Cindy H.; Vargesson, Neil; Figg, William D.
Abstract: Cereblon (CRBN) is a substrate recruiter element of the E3 cullin 4‐RING ubiquitin ligase complex, and a binding target of immunomodulatory agents (IMiDs). CRBN is responsible for the pleiotropic effects of IMiDs, yet its function in angiogenesis and in mediating the antiangiogenic effects of IMiDs remains unclear. We investigated the role of CRBN in the angiogenic process and in propagating the antiangiogenic effects of IMiDs in vitro. siRNA‐mediated CRBN knock down in human endothelial cells (HUVEC and HMVEC‐L), did not affect endothelial cell proliferation, migration, or tube formation. Using CRBN‐deficient mice, we further demonstrated that microvessal formation can occur independently of cereblon in the ex vivo mouse aortic ring model. The cereblon E3 ubiquitin ligase complex can recruit endothelial cell‐specific factors, AGO2 (associated with angiogenesis), and SALL4 (associated with embryogenesis/angiogenesis), for ubiquitin‐mediated degradation. Knockdown of CRBN caused a corresponding increase in AGO2 and SALL4 protein expression and IMiD treatment was able to rescue the siCRBN effect to increase the CRBN expression. These findings suggest one potential mechanism of action that likely involves a tightly coordinated regulation of CRBN with endothelial cell targets and highlight the need to further elucidate the mechanism(s), which could include cereblon‐independent pathways, through which IMiDs exert their antiangiogenic effects.